PENGARUH TERAPI OUTBOUND UNTUK MENINGKATKAN INTERAKSI SOSIAL SISWA SMA NEGERI 4 PEKANBARU - Nurrahfi, Era; Saam, Zulfan; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the description of students social interactions before and after being given outbound therapy, find out the differences in social interactions before and after being given outbound therapy and to find out how much influence the outbound therapy has to increase student social interaction. This search with experimental methods, the research design used is Pre-Experimental with one group pre-test and post-test approach. The subject in the study were 20 students taken by purposive sampling technique with the criteria for the result of social relations scale (questionnaire). The results showed that: (1) the social interactions of students before being given outbound therapy were mostly in the low category and after being given outbound therapy were mostly in the high and very high categories. (2) There is a significant difference in the level of social interaction of students before and after aoutbound therapy is given. (3) there is a significant influence on students social interactions before and after aoutbound therapy is given.Key Words: The Effect of Outbound Therapy, Social Interaction